NATURE OF DISTRIBUTION AND FORMATION OF COAL BASINS IN MONGOLIA - Delegiin Bat-Erdene (Geological Issues, 2023)
This article adduces a new scheme of coal-bearing zonation and the results of complex research on the various age peat accumulations coal-bearing deposits. The analysis of the paleotectonic and paleogeographic conditions of peat accumulation allowed to expose the general evolution of development in accordance with which there distinguished 3 stages of coal-bearing structures development: pimary or preparatory stage, when the full compensation of the depresions by the sedimentation goes on: -middle stage-stage of mass peat accumulation process's stopping. These srages are the typical features of the coal-bearing structures development on the territory of Mongolia.